Surgical Correction of Carcinoid Heart Disease Improves Liver Function and 5-Hydroxyindoleacetic Acid Levels - Shah, Husnain Abbas; Sagar, Vandana; Hughes, Simon; Khanna, Amardeep; Yim, Ivan; Lodge, Freya; Singh, Harjot; Oelofse, Tessa; Ó'Súilleabháin, Críostóir; Venkataraman, Hema; Shetty, Shishir; Steeds, Richard; et al. (Frontiers in Surgery, 2022)
Introduction: Carcinoid heart disease (CHD) is a consequence of neuroendocrine tumours releasing 5-hydroxytryptamine (5-HT) into the systemic circulation, affecting right heart valves, causing fibrosis, and eventually right heart failure. The aim of this study was to determine the effect of valve-replacement on kidney function, liver function, and 5-hydroxyindoleacetic acid (5-HIAA) levels. Methods: A Retrospective study of 17 patients with CHD who had undergone heart-valve replacement surgery between 2010 and 2019, from the Queen Elizabeth Hospital Birmingham. 5-HIAA levels, liver, and kidney function were measured in addition to hepatic inferior vena cava (IVC) diameter and its relationship to carcinoid symptoms. Results: 11 patients were male and 6 were female. At time of surgery, average age was 66.6±8.1 years and average BMI was 25.8±5.5 Kg/cm2. 3/17 patients had one valve replaced, 13/17 had two replaced (tricuspid and pulmonary), and 1/17 had three replaced (tricuspid, pulmonary and aortic). There was a 31% average decline in 5-HIAA (799.8 (343.6-1078.0) to 555.3 (275.8-817.9), p = 0.011), a 35% decline in bilirubin (20 (16-29) to 13 (10-19), p = <0.001), and a 15% reduction in the short and long axes of the IVC after valve-replacement surgery (20.0 (18.0-25.0) and 36.5 (29.0-39.8) to 17.0 (14.5-19.3) and 31.0 (26.5-34.3) respectively, p = <0.001 and 0.002 respectively). Conclusion: Valve replacement surgery improves 5-HIAA levels alongside improved liver function and hepatic IVC diameter. These findings are consistent with resolution of congestive hepatopathy, and therefore enhanced clearance of 5-HIAA. This suggests that valve-replacement surgery can indirectly have beneficial outcomes on hepatic function and is also associated with a drop in the circulating levels of tumour derived serotonin.